2011
DOI: 10.1097/hcm.0b013e318225e03a
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Practice Nursing, Health Care Teams, and Perceptions of Team Effectiveness

Abstract: This article summarizes the results of an extensive review of the organizational and health care literature of advanced practice nursing (APN) roles, health care teams, and perceptions of team effectiveness. Teams have a long history in health care. Managers play an important role in mobilizing resources, guiding expectations of APN roles in teams and within organizations, and facilitating team process. Researchers have identified a number of advantages to the addition of APN roles in health care teams. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 93 publications
0
27
0
2
Order By: Relevance
“…According to the literature [1517], more effective teams generate better treatment outcomes and greater satisfaction among users. Effective teamwork also reduces health costs [18] and medical errors [19] and contributes to job satisfaction among staff [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [1517], more effective teams generate better treatment outcomes and greater satisfaction among users. Effective teamwork also reduces health costs [18] and medical errors [19] and contributes to job satisfaction among staff [15, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…The study findings support the processes identified by Kilpatrick et al . (). Other researchers have identified the important role of communication and care coordination in well‐functioning teams, and this may reflect their central role in team effectiveness (Salas et al .…”
Section: Discussionmentioning
confidence: 97%
“…ACNP roles include clinical, research, education and administrative components (Kilpatrick et al . ). NPs in most jurisdictions in Canada are authorised to (1) diagnose a disease or condition, (2) suggest and interpret tests and (3) prescribe medications (DiCenso et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Processes like communication and decision‐making have been identified as key factors in perceptions of team effectiveness (Kilpatrick et al. 2011).…”
Section: Introductionmentioning
confidence: 99%